Mewujudkan Ketahanan Pangan Lokal dengan Strategi Pengendalian Alih Fungsi Lahan Sawah - Purwandari, Sisca Putri; Martanto, Rochmat; Sapardiyono, Sapardiyono; Alfons, Alfons (Sekolah Tinggi Pertanahan Nasional, 2025)
The rate of conversion of agricultural land to non-agricultural uses in Kaliwates District, Jember Regency, is increasing along with population growth, urbanization, and economic development—threatening the sustainability of local food security. This study aims to (1) analyze the suitability of Protected Rice Fields (LSD) with actual land use, (2) identify the factors causing land use conversion, and (3) formulate control strategies through LSD policies. The data used includes LSD maps, 2023 land use maps, population density data, LSD areas, and land production. The analysis method consists of spatial overlay to measure the level of land use suitability and multiple linear regression to test the influence of variables causing land use conversion. The results show that 73.44% of the LSD area is suitable for land use, while 26.57% is not. The variables of LSD area and land production have a significant effect on the tendency of land use conversion, while population density does not show a significant effect in the tested model. Based on these findings, a control strategy was formulated that includes evaluation of LSD policies, optimization of spatial planning, intensification of production on still productive land, economic incentives to maintain agricultural functions, synchronization of sectoral databases, and strengthening of cross-agency coordination. These findings are expected to be a reference for formulating more effective policies for maintaining sustainable food agricultural land in areas with high urbanization pressures. Laju alih fungsi lahan pertanian menjadi non-pertanian di Kecamatan Kaliwates, Kabupaten Jember, meningkat seiring pertumbuhan penduduk, urbanisasi, dan perkembangan ekonomi—mengancam keberlanjutan ketahanan pangan lokal. Penelitian ini bertujuan untuk (1) menganalisis kesesuaian Lahan Sawah yang Dilindungi (LSD) dengan penggunaan lahan aktual, (2) mengidentifikasi faktor penyebab alih fungsi lahan, dan (3) merumuskan strategi pengendalian melalui kebijakan LSD. Data yang digunakan meliputi peta LSD, peta penggunaan lahan tahun 2023, data kepadatan penduduk, luas LSD, dan produksi lahan. Metode analisis terdiri dari overlay spasial untuk mengukur tingkat kesesuaian penggunaan lahan dan regresi linier berganda untuk menguji pengaruh variabel penyebab alih fungsi. Hasil menunjukkan bahwa 73,44% luas LSD sesuai dengan penggunaan lahan, sedangkan 26,57% tidak sesuai. Variabel luas LSD dan produksi lahan berpengaruh signifikan terhadap kecenderungan alih fungsi lahan, sedangkan kepadatan penduduk tidak menunjukkan pengaruh yang signifikan dalam model yang diuji. Berdasarkan temuan tersebut dirumuskan strategi pengendalian yang mencakup evaluasi kebijakan LSD, optimalisasi tata ruang, intensifikasi produksi pada lahan yang masih produktif, insentif ekonomi untuk mempertahankan fungsi pertanian, sinkronisasi basis data sektoral, serta penguatan koordinasi lintas instansi.Temuan ini diharapkan menjadi acuan perumusan kebijakan yang lebih efektif dalam mempertahankan lahan pertanian pangan berkelanjutan di daerah dengan tekanan urbanisasi tinggi.